Rural-Urban Differentials in Consumption Pattern Among Selected Households in Coimbatore City. - Geetha, K.T (2012)
The present study attempts to analyze the consumption habits of the households in rural and urban areas to understand the changes taking place in the consumption pattern of the households and to what extent these changes ensures the nutritional security of the households. The required data was collected from 50 households residing in Boluvampatti village and 50 households in Ganapathy town in Thondamuthur block. The results indicated consumption standards of the rural households were below the recommended threshold level of consumption leading to food and nutritional insecurity. Low expenditure elasticity for cereals and high expenditure elasticity for other food items signifies a shifting food consumption pattern in rural areas. A high calorie share of cereals in the total calorie intake in both rural and urban households signify the increasing dependence of the households on cereals for meeting their energy requirement.